Artificial skin with biological sensing and wound repairing capabilities and preparation method thereof

By using the combination of collagen-graphene oxide composite hydrogel film and polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film in artificial skin, the problem of insufficient mechanical properties of existing artificial skin materials is solved, and biological The functions of perception and wound repair enhance the antibacterial and promote repair capabilities of the material.

CN119236175APending Publication Date: 2025-01-03TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411251615.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-16
Filing Date
2024-09-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The mechanical properties of existing artificial skin materials are insufficient, resulting in easy damage in practical applications, and the antibacterial and pro-repair properties of graphene oxide in biomedical materials have not been fully developed.

Method used

The collagen-graphene oxide composite hydrogel film is used as the skin repair layer, and the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film is used as the electrosensing layer. A multi-layer superimposed grid-like structure is formed through 3D printing technology. Enhance the mechanical properties and biological perception of materials.

Benefits of technology

It realizes the biosensing function of artificial skin, can detect bioelectric information around the skin wound, has antibacterial and promotes repair capabilities, and improves the mechanical properties and biocompatibility of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236175A_ABST
    Figure CN119236175A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and provides an artificial skin with biological perception and wound repair capabilities and a preparation method thereof.The artificial skin comprises a skin repair layer, an isolation layer and an electric sensing layer, and the skin repair layer is a 3D printed collagen graphene composite hydrogel film; the isolating layer is a polyurethane film; and the electric sensing layer is a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film. The artificial skin provided by the invention can achieve a skin repairing effect through electrical stimulation and collagen materials; the electric sensing layer senses the pressure change of the skin wound surface and converts the pressure change into the change of an electric signal, so that the wound condition is detected; the artificial skin also has continuous antibacterial activity, can prevent wound infection, can effectively promote healing of soft tissue injury wounds, and improves tissue regeneration and repair capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to an artificial skin with biosensor effect and wound repair effect, in particular to an artificial skin with biosensing and wound repairing capabilities and a preparation method thereof. Background Art

[0002] After human skin is traumatized, the skin tissue on the surface of the wound will have varying degrees of necrosis. In order to promote faster wound healing, the use of artificial skin is a common and effective method. As a substitute for autologous skin transplantation, artificial skin can be used to treat wounds with damaged dermis, chronic wounds or burn wounds, and has the effects of promoting wound healing and reducing scar formation. Therefore, artificial skin should be biocompatible, maintain a moist environment, and maintain temperature. In order for the dressing to further fill the wound and promote the wound healing speed, this requires that in addition to satisfying the functions of common artificial skin in clinical practice, the inner dressing should also have the function of analyzing the healing stage of the wound and promoting wound cell regeneration; while the outer dressing should be hydrophobic, heat-insulating, and able to exchange gases with the environment.

[0003] As one of the main components of the human body, collagen is the first choice for artificial skin repair materials due to its low immunogenicity, good biocompatibility and biodegradability. However, a major problem faced by many existing artificial skin repair materials is that the mechanical properties of the materials are not good enough.

[0004] Graphene oxide has a significant antibacterial effect, good electrical conductivity, and can improve the mechanical properties of general biomaterials. However, graphene oxide also has certain cytotoxicity and is difficult to degrade in vivo. At present, the application of graphene oxide in biomedical materials is mainly focused on its electrical properties, and its antibacterial and repair-promoting properties are still to be developed.

[0005] At present, the printing ink used for bioprinting artificial skin is usually hydrogel, which includes natural polymer materials such as gelatin, hyaluronic acid, sodium alginate and chitosan, as well as synthetic polymers with good biosafety such as polyethylene glycol. However, bioprinting artificial skin made of hydrogel ink materials is limited by the mechanical properties of hydrogel, and the mechanical properties of artificial skin are weak, which is easy to be damaged in actual use. Summary of the invention

[0006] The purpose of the present invention is to provide an artificial skin with biological perception and wound repair capabilities and a preparation method thereof, which can overcome the defects of artificial skin made of existing materials and enable artificial skin to have biological perception and wound repair capabilities.

[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: An artificial skin with biological sensing and wound repair capabilities, comprising a skin repair layer, an isolation layer, and an electrical sensing layer arranged in sequence from bottom to top; The skin repair layer is a collagen-graphene oxide composite hydrogel membrane; The isolation layer is a polyurethane film; The electrical sensing layer is a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film.

[0008] A method for preparing artificial skin with biological perception and wound repair capabilities comprises the following steps: S1. Preparing a collagen-graphene oxide composite hydrogel film, comprising: S11, preparing collagen-graphene oxide bio-ink; S12, using collagen-graphene oxide bio-ink and an extrusion 3D printer, extruding collagen-graphene oxide bio-ink strips on a polyurethane film, wherein the ink strips are arranged alternately in a cross pattern to form a multi-layer superimposed grid structure and then spread to print a collagen-graphene oxide composite hydrogel material; S13, the collagen-graphene oxide composite hydrogel material printed in step S11 is air-dried to obtain a collagen-graphene oxide composite hydrogel film, at which time the collagen-graphene oxide composite hydrogel film is attached to the polyurethane film; S2. Preparing a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film, comprising: S21, preparing graphene oxide solution, polyvinyl alcohol solution, and sodium hydroxide solution respectively; S22, adding dopamine to the graphene oxide solution to obtain a graphene oxide-dopamine solution, and then adding a sodium hydroxide solution to adjust the pH of the graphene oxide-dopamine solution to adjust the pH value of the graphene oxide-dopamine solution to 11; S23, subjecting the graphene oxide-dopamine solution obtained in step S22 to ultrasonic treatment, and stirring the solution until the solution becomes a uniform dark black solution; S24, the dark black solution obtained in step S23 is added to the polyvinyl alcohol solution, and stirred vigorously until uniform; S25, injecting the solution obtained in step S24 into a mold, and obtaining a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film after repeated freezing and thawing; S3. The polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film is laminated to the sticky surface of the polyurethane film to which the collagen-graphene oxide composite hydrogel film is attached to form a three-layer composite hydrogel film, i.e., an artificial skin with biological sensing and wound repair capabilities.

[0009] Furthermore, the step of preparing collagen-graphene oxide bio-ink in S11 is: S111. Dissolve bovine tendon collagen in acetic acid at 25° C. to prepare a collagen solution with a concentration of 15 mg / ml; S112, respectively preparing a graphene oxide solution, a carbodiimide solution and an N-hydroxysuccinyl solution; the concentration of the graphene oxide solution is 0.1 μg / ml; the concentration of the carbodiimide solution is 15 mg / ml; the concentration of the N-hydroxysuccinyl solution is 15 mg / ml; S113, slowly adding the graphene oxide solution obtained in step S112 to the collagen solution obtained in S111 to obtain a collagen-graphene oxide solution, wherein the volume ratio of the graphene oxide solution to the collagen is 30:1; then adding the carbodiimide solution and the N-hydroxysuccinyl solution to the collagen-graphene oxide solution, slowly stirring for a cross-linking reaction, the stirring temperature is 4-6°C, and the stirring time is 0.5h; wherein the volume ratio of the collagen-graphene oxide solution, the carbodiimide solution, and the N-hydroxysuccinyl is 12:1:1; S114, centrifuging the mixture solution obtained in step 113 to obtain collagen-graphene oxide bio-ink; the centrifugal speed is 3000-5000 rpm, and the centrifugal time is 0.5 h.

[0010] Furthermore, the extrusion speed of the 3D printer in S12 is 1.5 mm / s and the printing speed is 2.5 mm / s.

[0011] Furthermore, in S21, the concentration of graphene oxide solution is 0.1 mg / ml, the concentration of polyvinyl alcohol solution is 0.1-0.2 g / ml, and the concentration of sodium hydroxide solution is 1 mol / L.

[0012] Furthermore, the mass ratio of dopamine added to S22 to graphene oxide is 1:1.

[0013] Furthermore, in S23, the ultrasonic temperature is 6-10°C, the ultrasonic time is 10-20 min, the stirring time is 2 h, and the stirring temperature is 60-65°C.

[0014] Furthermore, in S24, the stirring temperature is 60-65° C., and the stirring time is 6 h.

[0015] Furthermore, the thickness of the hydrogel mold silicone mold in S25 is 0.5~1 mm, and the number of freeze-thaw cycles is 3~5 times.

[0016] The beneficial effects of the present invention are: The artificial skin of the present invention can obtain bioelectric information around the skin wound, achieve a sensor effect, and detect the wound condition. At the same time, the artificial skin has the ability to resist bacteria, prevent infection, and promote repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a schematic diagram of the structure of the artificial skin of the present invention; In the figure, 1 is the skin repair layer; 2 is the isolation layer; 3 is the electrical sensing layer; Figure 2 is a flow chart of the preparation of artificial skin of the present invention; Figure 3 is a macroscopic image of the artificial skin material prepared in Example; Figure 4 is a SEM image of the electric sensing layer and the skin repair layer in the embodiment; Figure 5 It is a light microscopic image of the skin repair layer; Figure 6 is a stress-strain curve diagram of the artificial skin material prepared in the embodiment; Figure 7 is a swelling diagram of the collagen-graphene oxide composite hydrogel film prepared in the example; Figure 8 is a swelling diagram of the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film prepared in the example; Fig. 9 This is a CCK-8 test result diagram of the artificial skin material of the present invention; Fig.10 is a live and dead cell staining diagram of the artificial skin material of the present invention; Fig.11 is a strain sensing diagram of the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film prepared in the example; Fig.12 3 is a graph showing the cyclic tensile resistance change of the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film prepared in the example. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0019] like Figure 1 As shown, an artificial skin with biological sensing and wound repair capabilities includes a skin repair layer 1, an isolation layer 2, and an electrical sensing layer 3 arranged in sequence from bottom to top; Among them, the skin repair layer 1 is a collagen-graphene oxide composite hydrogel film; the isolation layer 2 is a polyurethane film; and the electrical sensing layer 3 is a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film.

[0020] The preparation method of artificial skin with biological sensing and wound repair capabilities, the specific process is as follows Figure 2 As shown, the following steps are included: S1. Preparing a collagen-graphene oxide composite hydrogel membrane (Col-GO hydrogel membrane), the steps comprising: S11, preparing collagen-graphene oxide bio-ink, the steps comprising: S111. At 25°C, bovine tendon collagen was dissolved in acetic acid to prepare a collagen solution. The concentration of the collagen solution was 15 mg / ml and the concentration of the acetic acid was 0.525 mol / l. The acidic conditions provided by the acetic acid promoted the cross-linking of collagen. Meanwhile, the acidic environment also had the effect of eliminating wound inflammation and promoting repair. S112, respectively preparing a graphene oxide solution, a carbodiimide solution and an N-hydroxysuccinyl solution; the concentration of the graphene oxide solution is 0.1 μg / ml; the concentration of the carbodiimide solution is 15 mg / ml; the concentration of the N-hydroxysuccinyl solution is 15 mg / ml; S113, slowly adding the graphene oxide solution obtained in step S112 to the collagen solution obtained in S111, the volume ratio of the graphene oxide solution to the collagen solution is 30:1; then adding the carbodiimide solution and the N-hydroxysuccinyl solution to the collagen-graphene oxide solution, slowly stirring for cross-linking reaction; the stirring temperature is 4-6°C to promote, and the stirring time is 0.5h; wherein the volume ratio of the acetic acid collagen hydrogel, the carbodiimide solution, and the N-hydroxysuccinyl is 12:1:1; S114, centrifuging the mixture solution obtained in step 113 to remove bubbles to obtain collagen-graphene oxide bio-ink; the centrifugal speed is 3000-5000 rpm, and the centrifugal time is 0.5 h.

[0021] S12. Collagen-graphene oxide bio-ink and an extrusion 3D printer are used to extrude collagen-graphene oxide bio-ink strips on a polyurethane film (PU film). The ink strips are arranged alternately in a cross pattern to form a multi-layer superimposed grid structure and then spread to print collagen-graphene oxide composite hydrogel materials. The extrusion speed of the 3D printer is 1.5 mm / s and the printing speed is 2.5 mm / s. Printing at this speed can form uniform and appropriately wide hydrogel strips.

[0022] S13, air-drying the collagen-graphene oxide composite hydrogel material printed in step S11 to obtain a collagen-graphene oxide composite hydrogel film (Col-GO hydrogel film). At this time, the collagen-graphene oxide composite hydrogel film (Col-GO hydrogel film) is attached to the polyurethane film (PU film) to form a complete double-layer composite film structure, thereby avoiding the adhesion process of the two layers of materials.

[0023] S2. preparing a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film), comprising: S21, respectively preparing a graphene oxide solution, a polyvinyl alcohol solution, and a sodium hydroxide solution; wherein the concentration of the graphene oxide solution is 0.1 mg / ml, the concentration of the polyvinyl alcohol solution is 0.1-0.2 g / ml, and the concentration of the sodium hydroxide solution is 1 mol / L; S22, adding dopamine to the graphene oxide solution, the mass ratio of the added dopamine to the mass ratio of the graphene oxide being 1:1, to obtain a graphene oxide-dopamine solution, and then adding a sodium hydroxide solution to adjust the pH of the graphene oxide-dopamine solution, and adjusting the pH value of the dopamine mixture solution to 11, so that dopamine is generated by self-polymerization reaction to form polydopamine and the graphene oxide is functionalized to improve the conductivity and biocompatibility of the material; S23, after ultrasonic treatment of the dopamine mixture solution obtained in step S22, stirring until the solution becomes a uniform dark black solution; wherein the ultrasonic temperature is 6-10°C, the ultrasonic time is 10-20 min; the stirring temperature is 60-65°C, and the stirring time is 2 h. Low-temperature ultrasonic treatment is conducive to the dispersion and interaction of graphene oxide and dopamine; S24, adding the dark black solution obtained in step S23 to the polyvinyl alcohol solution, and vigorously stirring until uniform, the stirring temperature is 60-65°C, and the stirring time is 6 hours. Long-term stirring allows the graphene oxide-dopamine material and the polyvinyl alcohol solution to be uniformly mixed to form a graphene oxide-polydopamine-polyethylene material; S25. Inject the solution obtained in step S24 into a mold, and obtain a polyvinyl alcohol-polydopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) after repeated freezing and thawing.

[0024] S3. The polyvinyl alcohol-polydopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) is laminated to the sticky surface of the polyurethane film (PU film) attached with the collagen-graphene oxide composite hydrogel film (Col-GO hydrogel film) to form a three-layer composite hydrogel film, i.e., an artificial skin with biosensing and wound repair capabilities. Example 1

[0025] (1) Dissolve bovine tendon collagen in acetic acid at 25°C to prepare a collagen solution with a concentration of 15 mg / ml; (2) preparing a graphene oxide solution with a concentration of 0.1 mg / ml, and further diluting the obtained graphene oxide solution to obtain a graphene oxide solution with a concentration of 0.1 μg / ml; (3) preparing a carbodiimide solution with a concentration of 15 mg / ml; (4) Prepare a 15 mg / ml N-hydroxysuccinyl solution.

[0026] (5) Add 0.1 μg / ml graphene oxide solution to the collagen solution at a volume ratio of 30:1.

[0027] (6) Add the prepared carbodiimide solution and N-hydroxysuccinyl solution to the solution in (5) at a volume ratio of 12:1:1.

[0028] (7) The obtained solution in (6) was stirred at 4°C for 0.5 h to allow gelation.

[0029] (8) The mixture solution obtained in (7) was centrifuged at 5000 rpm for 10 min to remove bubbles and obtain collagen-graphene oxide bio-ink.

[0030] (9) Collagen-graphene oxide bio-ink was used to perform 3D printing on the surface of the PU film at an extrusion speed of 1.5 mm / s and a printing speed of 2.5 mm / s to obtain a 2-layer 30x40 collagen-graphene oxide composite hydrogel film material.

[0031] (10) The collagen-graphene oxide composite hydrogel film material is air-dried to obtain the result of combining the skin repair layer and the isolation layer, such as Figure 3 As shown in a.

[0032] (11) Dissolve 5 g of polyvinyl alcohol (PVA) in 45 ml of deionized water (DI) and stir vigorously at 95 °C until a homogeneous solution is formed; (12) 100 mg of graphene oxide (GO) was dispersed in deionized water (DI) and ultrasonicated for 60 min.

[0033] (13) 100 mg of dopamine hydrochloride was added to the deionized water obtained in (12), and the pH value of the mixture was adjusted to 11 using 1 mol / l NaOH solution, followed by sonication in an ice bath for 10 min.

[0034] (14) The mixture solution obtained in (13) was vigorously stirred at 65 °C for 2 h until the solution became dark black and homogeneous.

[0035] (15) The polyvinyl alcohol solution was added to the mixture solution obtained in (14) and magnetically stirred at 65 °C for about 6 h to obtain a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) material.

[0036] (16) The obtained polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) material was injected into the prepared glass-silicone mold by a syringe, wherein the thickness of the silicone pad in the mold was 1 mm.

[0037] (17) The mold injected with the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) material was placed in a freezer at -25 °C for 12 h, and then taken out and thawed in a refrigerator for 6 h. This was repeated three times to obtain a physically cross-linked polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film). Figure 3 As shown in b.

[0038] (18) The obtained skin repair layer and isolation layer, i.e., the sticky surface of the PU film with collagen-graphene oxide composite hydrogel film (Col-GO hydrogel film) attached and the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) were laminated to form a three-layer composite hydrogel film, i.e., artificial skin with biosensing and wound repair capabilities. Example 2

[0039] (1) The preparation of the skin repair layer and the isolation layer is the same as in Example 1; (2) Dissolve 10 g of polyvinyl alcohol (PVA) in 40 ml of deionized water (DI) and stir vigorously at 95 °C until a homogeneous solution is formed; (3) 100 mg of graphene oxide (GO) was dispersed in deionized water (DI) and ultrasonicated for 60 min; (4) 100 mg of dopamine hydrochloride was added to the deionized water obtained in (3), the pH value of the mixture was adjusted to 11 using 1 mol / l NaOH solution, and then sonicated in an ice bath for 10 min; (5) The mixture solution obtained in (4) was vigorously stirred at 65° C. for 2 hours until the solution became dark black and uniform; (6) adding the polyvinyl alcohol solution prepared in (2) to the mixture solution obtained in (5), and magnetically stirring at 65° C. for about 6 hours to obtain a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) material; (7) injecting the obtained polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) material into the prepared glass-silicone mold through a syringe, wherein the thickness of the silicone pad in the mold is 1 mm; (8) The mold injected with the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) material was placed in a freezer at -25°C for 12 h, and then taken out and thawed in a refrigerator for 6 h. This was repeated three times to obtain a physically cross-linked polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film). Figure 3 As shown in c; (9) The skin repair layer obtained in (1) and the isolation layer, i.e., the sticky surface of the PU film with the collagen-graphene oxide composite hydrogel film (Col-GO hydrogel film) and the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) were laminated to form a three-layer composite hydrogel film, i.e., an artificial skin with biosensing and wound repair capabilities. Example 3

[0040] (1) The preparation of the skin repair layer and the isolation layer is the same as in Example 1; (2) Dissolve 5 g of polyvinyl alcohol (PVA) in 45 ml of deionized water (DI) and stir vigorously at 95 °C until a homogeneous solution is formed; (3) 100 mg of graphene oxide (GO) was dispersed in deionized water (DI) and ultrasonicated for 60 min; (4) 100 mg of dopamine hydrochloride was added to the deionized water obtained in (3), the pH value of the mixture was adjusted to 11 using 1 mol / l NaOH solution, and then sonicated in an ice bath for 10 min; (5) The mixture solution obtained in (4) was vigorously stirred at 65° C. for 2 hours until the solution became dark black and uniform; (6) adding the polyvinyl alcohol solution to the mixture solution obtained in (5) and magnetically stirring at 65° C. for about 5 hours to obtain a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) material; (7) injecting the obtained polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) material into the prepared glass-silicone mold through a syringe, wherein the thickness of the silicone pad in the mold is 0.5 mm; (8) The mold injected with the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) material was placed in a freezer at -25°C for 12 h, and then taken out and thawed in a refrigerator for 6 h. This was repeated three times to obtain a physically cross-linked polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film). Figure 3 As shown in d; (9) The obtained skin repair layer and isolation layer, i.e., the sticky surface of the PU film with collagen-graphene oxide composite hydrogel film (Col-GO hydrogel film) and the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) were laminated to form a three-layer composite hydrogel film, i.e., artificial skin with biosensing and wound repair capabilities.

[0041] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

[0042] Depend on Figure 3 It can be seen that different polyvinyl alcohol concentrations and different silicone mold thicknesses have a significant effect on the crystallinity of polyvinyl alcohol molecules. The higher the polyvinyl alcohol concentration, the greater the silicone mold thickness, and the higher the opacity of the outer film.

[0043] Figure 4 is a SEM image of the electrical sensing layer and the skin repair layer in the embodiment, Figure 4 a is the electric sensing layer of Example 1; Figure 4 b is the electric sensing layer of Example 2; Figure 4 c is the electric sensing layer of Example 3; Figure 4 d. Figure 4 e. Figure 4 f is the images of the skin repair layer in Examples 1, 2 and 3 at different angles; it can be observed that the electric sensing layer material has a relatively high porosity, indicating that the electric sensing layer has the basic conditions for bioelectric perception; the skin repair layer material is relatively flat and is composed of a large number of collagen fibers.

[0044] Figure 5 Light microscopy of the skin repair layer; it can be seen that there are a large number of graphene oxide particles in the collagen fibers of the collagen-graphene oxide composite hydrogel film. The light microscopy results show that the graphene is relatively evenly dispersed in the collagen material and forms a bond with the collagen, which helps to improve the mechanical properties and antibacterial properties of the collagen material, and at the same time makes it have a certain conductivity.

[0045] Figure 6The stress test is performed on the three-layer composite hydrogel film obtained in Examples 1, 2, and 3, and the obtained stress-strain diagram is shown; it can be seen that as the concentration of polyvinyl alcohol (PVA) increases, the mechanical properties of the material gradually improve, while the film thickness has no obvious effect on the mechanical properties of the material. The tensile strengths of the materials obtained in Examples 1, 2, and 3 are 0.28 MPa, 0.77 MPa, and 0.27 MPa, respectively. The experiment shows that the material has good mechanical properties and can meet the requirements of artificial skin composite materials for mechanical properties.

[0046] Figure 7 This is a swelling diagram of the collagen-graphene oxide composite hydrogel membrane (Col-GO hydrogel membrane) prepared in Examples 1, 2, and 3. It can be seen that the swelling rate of the Col-GO hydrogel membrane is about 1800%. It can be shown that the Col-GO hydrogel membrane has good swelling properties, which enables it to absorb body fluids and other liquids around the wound.

[0047] Figure 8 This is a swelling diagram of the polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film (PVA-PDA-GO hydrogel film) prepared in Examples 1, 2, and 3. It can be seen that the swelling rate of the PVA-PDA-GO hydrogel film is about 400%.

[0048] Fig. 9 The CCK-8 graphs of the Blank group (the material is only the culture medium), the skin repair layer collagen-graphene oxide composite hydrogel membrane Col-GO experimental group (0.01wt%GO / 15wt%Col), and the electrical sensing layer polyvinyl alcohol-dopamine-graphene oxide composite hydrogel membrane PVA-PDA-GO experimental group (0.1wt%GO / 10wt%PVA) are shown in Figure 8. Fig. 9 The results show that the OD value of the skin repair layer collagen-graphene oxide composite hydrogel film experimental group is higher than that of the blank group; the OD value of the electric sensing layer polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film experimental group is lower than that of the blank group, but still greater than 80% of the OD value of the blank group. This shows that the repair layer material in the embodiment has good cell activity, while the electric sensing layer material has no obvious inhibitory effect on cell growth.

[0049] Fig.10 The live and dead cell staining images of the blank group (the material is only the culture medium), the skin repair layer collagen-graphene oxide composite hydrogel membrane Col / GO experimental group (0.01wt%GO / 15wt%Col), and the electrical sensing layer polyvinyl alcohol-dopamine-graphene oxide composite hydrogel membrane PVA / PDA / GO experimental group (0.1wt%GO / 10wt%PVA). Fig.10The results show that the cell density increases with the extension of culture time, indicating that the material can promote the proliferation of L929 (mouse fibroblasts), has good biological activity, and meets the requirements of artificial skin for the biocompatibility of materials.

[0050] CCK-8 detection experiments and live-dead cell staining experiments showed that artificial skin materials have a certain ability to repair skin tissue.

[0051] Fig.11 is the strain sensing diagram of the PVA / PDA / GO experimental group (0.01wt%GO / 10wt%PVA) of the electric sensing layer polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film in Example 1, Fig.11 The results show that the △R / R 0 The values ​​show a stable incremental response to the applied strain level of 10-30%, indicating that the electrical sensing layer in the experimental material has a certain sensing effect that varies with strain.

[0052] Fig.12 is a graph showing the cyclic tensile resistance change of the PVA / PDA / GO experimental group (0.01wt% GO / 10wt% PVA) of the electrical sensing layer polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film in Example 1. Fig.12 The results show that in the stress cycles of 10%, 20%, and 30%, the resistance of the material at the same position has no obvious change in 5 cycles of stretching, indicating that the material has a certain repeatable sensing effect.

Claims

1. An artificial skin with biological sensing and wound repair capabilities, characterized in that : including a skin repair layer, an isolation layer, and an electric sensing layer arranged in sequence from bottom to top; The skin repair layer is a collagen-graphene oxide composite hydrogel film; The isolation layer is a polyurethane film; The electric sensing layer is a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film.

2. The method for preparing an artificial skin having biological perception and wound repairing capabilities according to claim 1, characterized in that: The steps include: S1. Preparing a collagen-graphene oxide composite hydrogel film, comprising: S11, preparing collagen-graphene oxide bio-ink; S12, using collagen-graphene oxide bio-ink and an extrusion 3D printer, extruding collagen-graphene oxide bio-ink strips on a polyurethane film, wherein the ink strips are arranged alternately in a cross pattern to form a multi-layer superimposed grid structure and then spread to print a collagen-graphene oxide composite hydrogel material; S13, air-drying the collagen-graphene oxide composite hydrogel material printed in step S11 to obtain a collagen-graphene oxide composite hydrogel film, wherein the collagen-graphene oxide composite hydrogel film is attached to the polyurethane film; S2. Preparing a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film, comprising: S21, preparing graphene oxide solution, polyvinyl alcohol solution, and sodium hydroxide solution respectively; S22, adding dopamine to the graphene oxide solution to obtain a graphene oxide-dopamine solution, and then adding a sodium hydroxide solution to adjust the pH of the graphene oxide-dopamine solution, and adjusting the pH value of the dopamine mixture solution to 11; S23, subjecting the dopamine mixture solution obtained in step S22 to ultrasonic treatment, and stirring the solution until the solution becomes a uniform dark black solution; S24, adding the dark black solution obtained in step S23 to the polyvinyl alcohol solution, and stirring vigorously until uniform; S25, injecting the solution obtained in step S24 into a mold, and obtaining a polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film after repeated freezing and thawing; S3. The polyvinyl alcohol-dopamine-graphene oxide composite hydrogel film is laminated to the sticky surface of the polyurethane film to which the collagen-graphene oxide composite hydrogel film is attached to form a three-layer composite hydrogel film, i.e., an artificial skin with biological sensing and wound repair capabilities.

3. The method for preparing an artificial skin with biological perception and wound repair capabilities according to claim 2, characterized in that: The steps of preparing collagen-graphene oxide bio-ink in S11 are: S111. Dissolve bovine tendon collagen in acetic acid at 25°C to prepare a collagen solution with a concentration of 15 mg / ml; S112, respectively preparing a graphene oxide solution, a carbodiimide solution and an N-hydroxysuccinyl solution; the concentration of the graphene oxide solution is 0.1 μg / ml; the concentration of the carbodiimide solution is 15 mg / ml; the concentration of the N-hydroxysuccinyl solution is 15 mg / ml; S113, slowly adding the graphene oxide solution obtained in step S112 to the collagen solution obtained in S111 to obtain an acetate collagen hydrogel, wherein the volume ratio of the graphene oxide solution to the collagen solution is 30:1; then adding the carbodiimide solution and the N-hydroxysuccinyl solution to the acetate collagen hydrogel, slowly stirring for a cross-linking reaction, the stirring temperature is 4-6°C, and the stirring time is 0.5h; wherein the volume ratio of the acetate collagen hydrogel, the carbodiimide solution, and the N-hydroxysuccinyl solution is 12:1:1; S114, centrifuging the mixture solution obtained in step 113 to obtain graphene oxide-collagen hydrogel bio-ink; the centrifugal speed is 3000-5000 rpm, and the centrifugal time is 0.5 h.

4. The method for preparing an artificial skin with biological perception and wound repair capabilities according to claim 2, characterized in that: The extrusion speed of the 3D printer in S12 is 1.5 mm / s, and the printing speed is 2.5 mm / s.

5. The method for preparing an artificial skin with biological perception and wound repair capabilities according to claim 2, characterized in that: The concentration of the graphene oxide solution in S21 is 0.1 mg / ml, the concentration of the polyvinyl alcohol solution is 0.1-0.2 g / ml, and the concentration of the sodium hydroxide solution is 1 mol / L.

6. The method for preparing an artificial skin with biological perception and wound repair capabilities according to claim 2, characterized in that: The mass ratio of dopamine added to the S22 to graphene oxide is 1:

1.

7. The method for preparing an artificial skin with biological perception and wound repair capabilities according to claim 2, characterized in that: In the S23, the ultrasonic temperature is 6-10°C, the ultrasonic time is 10-20 min; the stirring time is 2 h, and the stirring temperature is 60-65°C.

8. The method for preparing an artificial skin with biological perception and wound repair capabilities according to claim 2, characterized in that: The stirring temperature in S24 is 60-65° C., and the stirring time is 6 h.

9. The method for preparing an artificial skin with biological perception and wound repair capabilities according to claim 2, characterized in that: The thickness of the hydrogel mold silicone mold in the S25 is 0.5-1 mm, and the number of freeze-thaw cycles is 3-5 times.